Performance of Geosynthetic-Reinforced and Cement-Fly Ash-Gravel Pile-Supported Embankments over Completely Decomposed Granite Soil: A Case Study - Lijun Wu (Advances in Materials Science and Engineering)
This paper presents a full-scale test of the high-speed railway embankment to investigate the performance of cement-fly ash-gravel (CFG) pile-supported embankments over completely decomposed granite (CDG) soils. The authors compared the embankments built on CDG soils reinforced by geogrid only and geogrid and CFG piles in terms of ground settlement, layer settlement, and pile efficacy. Experimental results show that the CFG pile-supported embankment built on CDG soils performs well. The soil arching of CFG piled reinforcement is effective and significantly increases with surrounding soil consolidation. Furthermore, the increase in the soil arching effect is heavily dependent on differential settlements between surrounding soils and piles. Five methods widely adopted in current designing were used to calculate the pile efficacy. The prediction for pile efficacy by the Nordic method, BS8006, and its modified version is significantly higher than measured values. By contrast, the calculation by the EBGEO and CA model method is more approximate to the measured results in both the pattern and the value at the end of construction. Therefore, the adaptability of the EBGEO and CA model method outperformed that of the Nordic method, BS8006, and its modified version. Finally, in this case, the CA model method was recommended to estimate the pile efficacy of CFG pile-supported embankments built on CDG soils.